APOE alleles' association with neurocognitive function differ across Hispanic background groups: Latino cognitive aging: From genes to daily function. (7th December 2020) - Granot‐Hershkovitz, Einat; Tarraf, Wassim; Kurniansyah, Nuzulul; Daviglus, Martha; Isasi, Carmen R; Kaplan, Robert; Lamar, Melissa; Perreira, Krista; Smoller, Sylvia; Stickel, Ariana; Thyagarajan, Bharat; Zeng, Donglin; et al.
Abstract: Background: Cognitive impairment, dementia, and Alzheimer's disease (AD) have higher rates in the Hispanic population compared to non‐Hispanic Whites. APOE alleles are the strongest known genetic predictors for AD, however, in the Hispanic population, the effect appears to be weaker, and inconsistent between studies. We hypothesized that this heterogeneity is due, in part, to ancestry‐specific genetic effects. Method: We investigated the associations of APOE alleles with cognitive decline and mild cognitive impairment (MCI), determined by longitudinal cognitive assessment 1 . The study population included 4, 250 individuals from the SOL‐INCA study, a subset of middle‐aged and older adults' from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We further stratified and explored these associations within six different Hispanic background groups: Cuban, Dominican, Mexican, Puerto‐Rican, South‐American, and Central‐American. Finally, we performed interaction analysis to study the hypothesis that proportion genetic ancestry (European, African and Amerindian) modifies the effect of the APOE alleles on the neurocognitive functions. Result: The APOE ε4 allele was associated with both global cognitive decline (Beta=‐0.11, p‐value= 0.01) and a status of 'cognitive decliner', defined when global cognitive decline is higher than expected in normal cognitive aging, (OR=1.15, p‐value=0.03). After stratification by background groups, these associations remained significant only for Cubans showing a stronger effect relative to the effect in the total population (Decliners: OR= 1.46, p‐value= 0.007, global cognitive decline: Beta= ‐0.25, p‐value= 0.01). Stratification analysis also revealed new associations showing protective effects on MCI and cognitive decline by the APOE ε2 allele in two of the Hispanic background groups: Dominican and Puerto‐Rican. Heterogeneity tests suggest a significant differential effect for global cognitive decline for both APOE ε2 (p‐value <0.001) and APOE ε4 (p‐value <0.05). Interaction analysis suggests that increased proportion of African genetic ancestry was associated with a more protective effect conferred by APOE ε2 on global cognitive decline. Also, an increased proportion of Amerindian genetic ancestry was associated with lower risk effects conferred by APOE ε4 on both decline phentoypes. Conclusion: These results suggest that APOE alleles' effects on neurocognitive functions differ across the six Hispanic genetic backgrounds and are modified by ancestry‐specific genetic effects.